‘Adaptation of Traditional Screen Art’ – online theatres: a chance to explore new frontiers - Othman, Mohd Sukki; Abu Bakar, Roslina (Human Resource Management Academic Research Society, 2022)
Adaptation of traditional screen art’ is an effort put forth by the students of Malay Folklore to present the folklore stories from oral methods to an online theater production. It imposes to bring an impact to the society with the understanding of concepts as well as the value of the myriad traditional folk literature within the country. By showcasing this online theatre, fresh new ideas are bursting and bubbling in the minds of these students as initiatives in ensuring the interests and assets of the Malay literature in Malaysia is up for further developments by upcoming generations. This study consists of the two objectives. First, to display the skill of students where students can balance aspects of physical, emotional, spiritual, intellectually and personality. Secondly, to analyzing student soft skills. Therefore, this study applies the observation method to study the changes in the behavior among the students. As a result, this study proved that `adaptation of traditional screen art’ serves as a platform where students can gain knowledge as well as new experiences in the performing arts industry especially ones that are concerned with Malaysian folklores and fairy tales. In addition to that, students are also exposed on the ropes on how to improvise and showcase these wonderful Malay literary works on stage. Such efforts to put forth a production will act as a learning process, where the students are able to truly understand and appreciate these magnificent literatures. Through this effort, the students are instilled with all the soft skills needed, from matters of management as well as the creation of performing oral traditions virtually. Findings from this research can display students' skills in creating virtual oral traditions that ultimately form students' soft skills. Hopefully further researchers can expand the study of oral tradition and its benefits among the new generation. In addition, being able to connect it with multimedia elements and technology.